End-to-End Delay QoS Attribute-Based Bundling Strategy of Wireless Improved Reverse Charging Network Pricing Model - Fitri Maya Puspita; Ayu Wulandari; Evi Yuliza; Robinson Sitepu; Yunita Yunita (Science and Technology Indonesia, 2021)
In this article, a multi-link internet reverse charging (IRC) scheme model in a multi-service network with the addition of a bundling strategy is proposed. Reverse charging schemes in multi-link and multi-service networks are rarely discussed in previous studies. This financing scheme is designed with the aim of maximizing service provider profits by minimizing internet usage costs. The basic cost and satisfaction level of the service provided by the ISP is focused on this effort. The model formed in this study is a Mixed Integer Non-Linear Programming (MINLP) model that is completed using software LINGO 13.0. This problem comprises two cases, when α case as a parameter and β as a parameter and or variable with sub–cases increases in usage based financing schemes. Thus, the results obtained can be a consideration for ISPs in determining the price of services that can support an ISP. The updated IRC model provides a more optimal solution than the original IRC model.